The ‘Butterfly Effect’: Identifying pathways for sustainability transformation through social processes of disaster resilience - Belinda Jane Davis; Alan Reid; Briony Rogers (Global Sustainability)
Abstract Non-technical summary We reviewed published research on natural hazards and community disaster resilience to identify how relationships between people and their experiences of disaster interact to shape possibilities for positive transformative change. Research commonly analyzes processes within and across individual and collective or structural spheres of a social system, but rarely investigates interactions across all three. We present a framework focused on ‘spheres of influence’ to address this. The Framework shows how positive relationships that prioritize restoring shared, meaningful and purposeful identities can lead to expansive and incremental capacity for transformative outcomes for sustainability: a process we liken to the butterfly effect.